2014
DOI: 10.1007/s10584-014-1199-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ice phenology characteristics of two Central European steppe lakes from 1926 to 2012 - influences of local weather and large scale oscillation patterns

Abstract: Ice cover of the two Central European steppe lakes, Lake Balaton (Hungary) and Lake Neusiedl (Austria/Hungary), is characterized by high interannual variability (mean ice duration ± s.d.: 44±26 days and 73±28 days, respectively). For both lakes, a trend towards shorter ice duration and earlier ice-off can be observed in the 86 and 81 year data records, respectively. For Lake Neusiedl, significant trends for ice-on (+2.3 days decade −1 ), ice-off ( −1.8 days decade −1 ) and ice duration ( −3.1 day decade −1 ) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
3
8
1
1
Order By: Relevance
“…We found that 97% of lakes exhibited earlier ice breakup dates across the northern hemisphere from 1951 to 2014. These trends are consistent with regional and global ice phenology studies indicating a period of climate warming over the past few decades (e.g., Anderson et al ; Magnuson et al ; Benson et al ; Soja et al ). Specifically, warming spring air temperature was the primary driver of earlier ice breakup dates, but differences in elevation also explained some of the variation in ice breakup at the global level.…”
Section: Discussionsupporting
confidence: 89%
“…We found that 97% of lakes exhibited earlier ice breakup dates across the northern hemisphere from 1951 to 2014. These trends are consistent with regional and global ice phenology studies indicating a period of climate warming over the past few decades (e.g., Anderson et al ; Magnuson et al ; Benson et al ; Soja et al ). Specifically, warming spring air temperature was the primary driver of earlier ice breakup dates, but differences in elevation also explained some of the variation in ice breakup at the global level.…”
Section: Discussionsupporting
confidence: 89%
“…The results relating to the trends in ice phenomena were contrary to those observed in the present study: it was found that freeze-up has not changed, 15 break-up has shifted earlier by 7 days/100 years, and the duration of ice-cover has decreased by 12 days/100 years (Soja et al, 2014). This discrepancy calls attention to the importance of a common reference period in trend analysis and climate research.…”
Section: Regional and Global Outlookcontrasting
confidence: 99%
“…This is also agrees with the research by Franssena and Sherrer (2008) who analysed the ice regimes of 11 lakes situated in the Swiss plateau and stated that ice cover duration has changed as the air temperature in winter is higher than it used to be. The research team studying Lake Balaton (Hungary) and Lake Neusiedl (Austria/Hungary) observed a very similar situation, and the average duration of ice cover was 44 and 73 days respectively, with a large interim variability (Soja et al 2014). Obviously, the ice cover duration is longer in the northern part of Europe -ice covers the surface of Lake Kilpisjärvi for 222 days, yet even here we can observe some modifications resulting from global warming (Lei et al 2012).…”
Section: Discussionsupporting
confidence: 59%
“…2014). However, in the case of a lack of such data, other long-term periods are used Ptak et al 2019;Nowak et al 2018;Kainz et al 2017;Lei et al 2012;Soja et al 2014) in order to determine the ice regimes of selected lakes, which are largely affected by climate change (Smekhtin 2017).…”
Section: Discussionmentioning
confidence: 99%